2001
DOI: 10.1128/iai.69.4.2612-2620.2001
|View full text |Cite
|
Sign up to set email alerts
|

Complete DNA Sequence and Comparative Analysis of the 50-Kilobase Virulence Plasmid of Salmonella enterica Serovar Choleraesuis

Abstract: The complete nucleotide sequence of pKDSC50, a large virulence plasmid from Salmonella enterica serovar Choleraesuis strain RF-1, has been determined. We identified 48 of the open reading frames (ORFs) encoded by the 49,503-bp molecule. pKDSC50 encodes a known virulence-associated operon, the spv operon, which is composed of genes essential for systemic infection by nontyphoidal Salmonella. Analysis of the genetic organization of pKDSC50 suggests that the plasmid is composed of several virulence-associated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 61 publications
2
40
2
1
Order By: Relevance
“…The 49,503-bp pSCV contained 48 ORFs (43,77), and the 93,939-bp pSTV contained 108 ORFs molecules (96). Comparison of the two plasmids reveals that they are closely related (37,38).…”
Section: Bacterial Geneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 49,503-bp pSCV contained 48 ORFs (43,77), and the 93,939-bp pSTV contained 108 ORFs molecules (96). Comparison of the two plasmids reveals that they are closely related (37,38).…”
Section: Bacterial Geneticsmentioning
confidence: 99%
“…b DNA sequence differs from that of pSTV (77 terial load in the vicinity of the epithelial cell lining. The pef operon is a 7-kb region containing genes for plasmid-encoded fimbriae (57).…”
Section: Bacterial Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have sequenced ORF and upstream region of slyA of several serovars of Salmonella, and found that all of the serovars so far examined use the sequence TTG as initiation codon of slyA, and the nucleotide sequences of this region were highly conserved (14). In our study of Salmonella virulence, S. serovar Choleraesuis has been mainly used (1,11,13,18), because this serovar shows a high tendency to cause systemic salmonellosis to human and swine compared with S. serovar Typhimurium (2,25), and the genes responsible for systemic salmonellosis are expected to be studied in simpler system by using this serovar. In this context the function of slyA in S. serovar Choleraesuis has been investigated in relation to our previous and ongoing studies on the pathogenesis of this serovar.…”
mentioning
confidence: 99%
“…For the full expression of the Salmonella virulence, many classes of virulence genes such as inv genes (7), pag genes (10), and plasmid-encoded spv genes (9,11) are required. Among them regulatory genes are of highest importance for the timely expression of the virulence genes to adapt to the environmental changes during the infection process.…”
mentioning
confidence: 99%